Pengaruh Harga, Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Konsumen Berbelanja Pada Djaros Swalayan Jati Pariaman - Eldhani, Gufran; Yanti, Novi; Zaki, Zaki (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2023)
This study aims to determine the effect of price, service quality and product quality on consumer shopping satisfaction at Djaros Swalayan Jati Pariaman partially and simultaneously. This research was conducted in Kota Pariaman using primary and secondary data, with multiple linear analysis techniques. Based on the partial results (T test) the price variable (X1) is 0.005 <0.05, the service quality variable (X2) is 0.002 <0.05 and the product quality variable (X3) is 0.004 <0.5 which means it has a significant influence on satisfaction Consumer (Y) Shops at Djaros Swalayan Pariaman. Simultaneously (F test) Fcount value 3.408 > FT table 2.70 and Sig. 0.021 is less than <0.05 which means it has a significant effect simultaneously on shopping satisfaction (Y) at Djaros Supermarkets. The value of the coefficient of determination symbolized R2 (R-Square) is 0.584, in other words, the large percentage of variation in Consumer Satisfaction (Y) of Djaros Swalayan Pariaman can be explained by variations of the three independent variables, namely Price (X1) Service Quality (X2) and Product Quality (X3) of 58.40% while the remaining 41.60% is explained by other variables outside of this research.